2021
DOI: 10.5812/ijem.110234
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Parathyroid Carcinoma: An Unusual Clinical Presentation and Mini-review

Abstract: Introduction: Primary hyperparathyroidism (PHPT) is a rare condition in the pediatric population. Parathyroid carcinoma (PC) is a very uncommon cause of PHPT, accounting for < 1% of pediatric PHPT cases. It is challenging to distinguish between parathyroid adenoma (PA), the most common cause of PHPT, and PC. In this report, we described a young female who presented with a history of progressive limping and was finally diagnosed with PC. Case Presentation: A 15-year-old girl presented with progressive limpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…As expected from the data on adults diagnosed with a parathyroid carcinoma, this exceptional histological entity (that is described in less than 1% of pediatric cases with PHP) is associated with very high PTH values [72,73]. For instance, Rahimi et al [73] reported on a 15-year-old female who initially presented with a PTH level of 2876 pg/mL (the immunohistochemistry report showed a Ki67 of 2-3%, and positive CK and CD31 reactions) [73]. The same authors [73] performed an analysis of published cases (from 1972 to 2020) and found 17 reports of parathyroid carcinoma in the pediatric population; total serum calcium varied between 12 and 20.7 mg/dL, and PTH levels were between 300 and 8638 pg/mL (the ages reported were between 8 and 16 years; the male to female ratio was 0.6; 60% of these children had palpable neck tumors; 50% of them displayed various bone complications; one out of five subjects had distant metastases, particularly pulmonary and lymphatic) [73].…”
Section: Lab Findingsmentioning
confidence: 54%
See 3 more Smart Citations
“…As expected from the data on adults diagnosed with a parathyroid carcinoma, this exceptional histological entity (that is described in less than 1% of pediatric cases with PHP) is associated with very high PTH values [72,73]. For instance, Rahimi et al [73] reported on a 15-year-old female who initially presented with a PTH level of 2876 pg/mL (the immunohistochemistry report showed a Ki67 of 2-3%, and positive CK and CD31 reactions) [73]. The same authors [73] performed an analysis of published cases (from 1972 to 2020) and found 17 reports of parathyroid carcinoma in the pediatric population; total serum calcium varied between 12 and 20.7 mg/dL, and PTH levels were between 300 and 8638 pg/mL (the ages reported were between 8 and 16 years; the male to female ratio was 0.6; 60% of these children had palpable neck tumors; 50% of them displayed various bone complications; one out of five subjects had distant metastases, particularly pulmonary and lymphatic) [73].…”
Section: Lab Findingsmentioning
confidence: 54%
“…As expected from the data on adults diagnosed with a parathyroid carcinoma, this exceptional histological entity (that is described in less than 1% of pediatric cases with PHP) is associated with very high PTH values [72,73]. For instance, Rahimi et al [73] reported on a 15-year-old female who initially presented with a PTH level of 2876 pg/mL (the immunohistochemistry report showed a Ki67 of 2-3%, and positive CK and CD31 reactions) [73].…”
Section: Lab Findingsmentioning
confidence: 85%
See 2 more Smart Citations
“…Dieses Verhältnis ändert sich jedoch bei Betrachtung der Gruppe mit kritischer Hyperkalzämie und hyperkalzämischer Krise. Hier werden vermehrt atypische Adenome und NSD-Karzinome gefunden [41,43,48,49,55,56,57]. So berichteten Gurrado et al [53] in einer Literaturrecherche von 499 Patient*innen mit hyperkalzämischer Krise, dass bei 32 von 318 Patient*innen (10,1 %) ein NSD-Karzinom nachgewiesen wurde.…”
Section: Histologie Der Nebenschilddrüsenerkrankung Bei Hyperkalzämis...unclassified